A polyvinylidene fluoride / polar polymer composite and a method for preparing the same

CN120737528BActive Publication Date: 2026-10-16WANHUA CHEM GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511084224.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2026-10-16
Estimated Expiration
2045-08-04

AI Technical Summary

Technical Problem

[0003]然而,PVDF与PA间的界面相容性问题比较突出,PVDF和PA因极性差异较大导致共混材料容易分层

Benefits of technology

[0034] The method for preparing PVDF/polar polymer composite materials provided in this application involves adjusting the decomposition temperature (t) to achieve the desired temperature. 1/2 =0.1h) The first initiator with a temperature not lower than 110℃ and a decomposition temperature (t 1/2 A second initiator with a temperature of less than 110℃ (=0.1h) is compounded in a certain proportion, so that the compound initiator slowly decomposes in the first zone (i.e., the low temperature zone) of the extruder to generate primary free radicals, which then initiate the rapid grafting of modified monomers in the second zone (i.e., the high temperature zone). This significantly increases the concentration of free radicals and the activation time, reduces the activation energy of the grafting reaction, realizes the controllable grafting of modified monomers on PVDF, and improves the grafting rate, thereby effectively improving the interfacial compatibility problem between PVDF and polar polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005531924010000051
    Figure BDA0005531924010000051
  • Figure BDA0005531924010000061
    Figure BDA0005531924010000061
  • Figure BDA0005531924010000062
    Figure BDA0005531924010000062
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and discloses a polyvinylidene fluoride / polar polymer composite material and a preparation method thereof. The preparation method comprises the following steps: mixing a polar polymer, polyvinylidene fluoride, a modified monomer and a compounded initiator, and then adding the mixture into an extruder; the reaction temperature of a first zone of the extruder is controlled to be 175 DEG C to 185 DEG C, and the reaction temperature of a second zone of the extruder is controlled to be 205 DEG C to 215 DEG C; the obtained material is cooled, granulated and dried to obtain the polyvinylidene fluoride / polar polymer composite material. Two initiators with different decomposition temperatures are compounded in a certain proportion, the compounded initiator slowly decomposes to generate primary free radicals in the first zone of the extruder, the modified monomer is rapidly grafted in the second zone, the free radical concentration and the activity time are significantly improved, the grafting reaction activation energy is reduced, the controllable grafting of the modified monomer on the polyvinylidene fluoride is realized, the grafting rate is improved, and the interface compatibility problem of the polar polymer and the polyvinylidene fluoride can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer materials technology, specifically to a polyvinylidene fluoride / polar polymer composite material and its preparation method. Background Technology

[0002] With the increasing demand for energy, the safety and durability of oil and gas pipelines have become critical challenges. Polyamide (PA), as a commonly used barrier material, possesses good mechanical properties and chemical stability, but it is prone to hydrolysis under high temperature and pressure environments, leading to pipeline performance degradation. To improve barrier performance, polyvinylidene fluoride (PVDF) can be laminated into the inner layer of PA pipelines. The hydrolysis resistance and chemical corrosion resistance of PVDF material can effectively compensate for the shortcomings of PA material.

[0003] However, the interfacial compatibility between PVDF and PA is a significant issue. The large polarity difference between PVDF and PA makes the blended materials prone to stratification. Traditional physical blending methods struggle to achieve molecular-level dispersion, while grafting modification technology offers a new approach to interface optimization. Studies have shown that techniques such as ionizing radiation grafting and solution grafting typically require additional post-processing steps, resulting in complex processes and demanding conditions. However, existing melt grafting schemes suffer from low grafting rates (<5%).

[0004] Therefore, it is essential to improve the interfacial compatibility between polymers, such as PVDF / PA, and develop PVDF / polar polymer composites that combine high compatibility, high hydrophilicity, and high strength to meet the needs of fields such as oil and gas barrier and pipeline transportation. Summary of the Invention

[0005] In view of this, the primary objective of this application is to provide a method for preparing PVDF / polar polymer composite materials to effectively improve the interfacial compatibility between PVDF and polar polymers.

[0006] Another objective of this application is to provide a PVDF / polar polymer composite material with good hydrophilicity and high strength.

[0007] According to embodiments of this application, in a first aspect, a method for preparing a PVDF / polar polymer composite material is provided, comprising the following steps:

[0008] S1. Mix PVDF, polar polymer, modified monomer and compound initiator to form a mixture;

[0009] The compound initiator comprises a first initiator and a second initiator in a mass ratio of 1 to 3:1, wherein the decomposition temperature T1(t) of the first initiator is... 1 / 2 =0.1h) not lower than 110℃, the decomposition temperature T2 (t) of the second initiator 1 / 2=0.1h) less than 110℃;

[0010] S2. The mixture obtained in S1 is added to the extruder and reacted sequentially in the first and second zones of the extruder. The reaction temperature in the first zone is controlled at 175℃~185℃ and the reaction temperature in the second zone is controlled at 205℃~215℃.

[0011] S3. After cooling the material obtained in S2, granulate it and dry it to obtain a PVDF / polar polymer composite material.

[0012] It should be noted that the existing melt grafting technology uses high-temperature initiators to perform melt grafting at 170℃~190℃. The initiators have long half-lives, slow decomposition efficiency, low concentration of active free radicals, and low grafting rate, which has limited improvement on interfacial compatibility. If the concentration of high-temperature initiators is increased, it will lead to a high degree of cross-linking of the product, which will affect the product performance.

[0013] Therefore, this application combines a first initiator and a second initiator with different decomposition temperatures in a certain proportion, so that the combined initiator slowly decomposes in the first zone (i.e., the low-temperature zone) of the extruder to generate primary free radicals and initiate a preliminary reaction. Subsequently, it rapidly decomposes in the second zone (i.e., the high-temperature zone) to generate a large number of free radicals, which synergistically initiate the rapid grafting of modified monomers. This significantly increases the free radical concentration and activity time, reduces the activation energy of the grafting reaction, and increases the grafting rate, thereby effectively improving the interfacial compatibility problem of composite materials.

[0014] This study found that if the mass ratio of the first initiator to the second initiator is too small (less than 1:1), the concentration of active free radicals will be low, thereby reducing the grafting rate. Conversely, when the mass ratio of the first initiator to the second initiator is too large (greater than 3:1), the first initiator will decompose and fail too quickly due to the high reaction temperature, which will also affect the grafting rate. Furthermore, monomers with poor heat resistance are also prone to decomposition at higher temperatures. For example, sulfonic acid groups are prone to absorbing water and hydrolyzing into sulfate groups at high temperatures, which is not conducive to improving interfacial compatibility.

[0015] In this application, the term "t" 1 / 2 "t" refers to the half-life of an initiator, which is the time required for the initiator to decompose to half its initial concentration at a given temperature. It is used to measure the activity of the initiator or the magnitude of the reaction rate. 1 / 2 "=0.1h" indicates that the time required for the initiator to decompose to half of its initial concentration at a certain temperature is 0.1h. The aforementioned temperature is called the decomposition temperature of the initiator. That is, the decomposition temperature in this application is the temperature corresponding to the initiator having a half-life of 0.1h.

[0016] In this application, the term "polar polymer" refers to other polymeric materials with permanent dipolar properties, excluding PVDF, such as at least one of polyamide (PA), polycarbonate (PC), and polyethylene terephthalate (PET).

[0017] In some optional embodiments, the compound initiator accounts for 0.1% to 0.5% of the mass of the mixture, thus ensuring the quality and performance of the grafted product. If the mass concentration of the compound initiator is too high, the probability of free radical collisions increases, leading to more side reactions, which increases the degree of crosslinking of the grafted product and reduces the grafting rate. Conversely, if the mass concentration of the compound initiator is too low, the polymerization reaction rate will be slower, which will also lead to a lower grafting rate.

[0018] For example, the first initiator may be, for example, dicumyl peroxide (DCP, t 1 / 2 =0.1h corresponds to a decomposition temperature of 150±5℃), di-tert-butyl peroxide (DTBP, t 1 / 2 =0.1h corresponds to a decomposition temperature of 160±5℃), benzoyl peroxide (BPO, t 1 / 2 At least one of the following can be used: the decomposition temperature at 0.1 h is 115 ± 5 °C; the second initiator can be, for example, dimethyl azobisisobutyrate (AIBME, t 1 / 2 =0.1h corresponds to a decomposition temperature of 100±5℃), azobisisobutyronitrile (AIBN, t 1 / 2 At least one of the following: (the decomposition temperature corresponding to 0.1h is 100±5℃).

[0019] In some optional embodiments, the modified monomer includes sodium α-alkenylsulfonate, which comprises 5% to 10% by mass in the mixture. Sodium α-alkenylsulfonate utilizes the alkenyl group in its chemical structure to graft onto the PVDF backbone, while the sulfonic acid group can form hydrogen bonds with the polar groups in the polar polymer, thereby improving the interfacial compatibility between the polar polymer and PVDF. If the amount of modified monomer is too small, the improvement effect on the interfacial compatibility of the composite material will be insignificant; conversely, if the amount of modified monomer is too large, a large amount of monomer residue will remain, affecting product quality.

[0020] For example, the sodium α-alkenyl sulfonate may be at least one of sodium methacrylate sulfonate (SMAS), sodium acrylate sulfonate, and sodium ethylene sulfonate.

[0021] In some optional embodiments, the mass ratio of the polar polymer to the PVDF is 1 to 3:2. The polar polymer has poor hydrolysis resistance, while the PVDF is hydrolysis resistant. By combining the two, the composite material can have better hydrolysis resistance and oil and gas barrier properties.

[0022] For example, the polar polymer includes at least one of polyamide (PA), polycarbonate (PC), and polyethylene terephthalate (PET). Specifically, the polyamide may be at least one of PA6, PA66, PA46, PA56, PA612, PA610, PA1010, PA12, PA1212, PA1012, PA11, PA510, PA512, PA6T, PA5T, PA9T, PA10T, PA11T, PA12T, PA61, MXD6, MXD10, PPTA, and aramid 1313. This application employs a combination of a compound initiation system and segmented temperature control technology, which significantly improves the free radical concentration and activity time, enhances the grafting rate, and is compatible with different grades of PA, achieving better melt grafting to improve interfacial compatibility.

[0023] In some optional embodiments, the weight-average molecular weight of the PVDF is 200,000 to 400,000, which ensures suitable melt viscosity and strength, thereby guaranteeing product quality and performance. If the molecular weight of the PVDF is too large, the melt viscosity and strength will be too high, making it unsuitable for extrusion operations. Conversely, if the molecular weight of the PVDF is too small, the melt viscosity and strength will be correspondingly too low, resulting in low strength of the final product and affecting product performance.

[0024] In some optional embodiments, the mixture in S1 further includes a stabilizer, which comprises 0.1% to 0.45% by mass in the mixture. This stabilizer can neutralize the acidic substances byproducts of the grafting reaction, thereby promoting the smooth progress of the grafting reaction and preventing polymer decomposition and free radical capture under acidic catalysis, reducing ineffective free radical termination. If the stabilizer dosage is too high, a large amount of stabilizer will remain in the PVDF / polar polymer composite material, thus affecting the strength and apparent properties of the composite material.

[0025] For example, the stabilizer includes at least one of urea, calcium carbonate, and sodium carbonate.

[0026] In some alternative embodiments, the reaction time in S2 is 5–10 minutes to ensure a suitable grafting ratio. If the grafting reaction time is too long, it will lead to excessive cross-linking, affecting product quality and consequently reducing processability and toughness. Conversely, if the reaction time is too short, it will affect the grafting ratio, thus hindering the improvement of the composite material's interfacial compatibility.

[0027] In some alternative implementations, the extruder may be a twin-screw extruder, which enables continuous production and makes it possible to expand the application of PVDF.

[0028] According to an embodiment of this application, in a second aspect, a PVDF / polar polymer composite material prepared using the method described in the first aspect is provided.

[0029] In some alternative embodiments, the polyvinylidene fluoride / polar polymer composite material is a PVDF / PA composite material or a PVDF / PC composite material.

[0030] In some optional embodiments, the grafting rate of the polyvinylidene fluoride / polar polymer composite material is not less than 5.3%. This effectively improves the interfacial compatibility between PVDF and the polar polymer.

[0031] In some optional embodiments, the peel force between the polyvinylidene fluoride / polar polymer composite material and the polar polymer is not less than 4.2 N / 15 mm.

[0032] In some alternative embodiments, the water contact angle of the polyvinylidene fluoride / polar polymer composite material is not greater than 81.4°.

[0033] The technical solution of this application has the following advantages:

[0034] The method for preparing PVDF / polar polymer composite materials provided in this application involves adjusting the decomposition temperature (t) to achieve the desired temperature. 1 / 2 =0.1h) The first initiator with a temperature not lower than 110℃ and a decomposition temperature (t 1 / 2 A second initiator with a temperature of less than 110℃ (=0.1h) is compounded in a certain proportion, so that the compound initiator slowly decomposes in the first zone (i.e., the low temperature zone) of the extruder to generate primary free radicals, which then initiate the rapid grafting of modified monomers in the second zone (i.e., the high temperature zone). This significantly increases the concentration of free radicals and the activation time, reduces the activation energy of the grafting reaction, realizes the controllable grafting of modified monomers on PVDF, and improves the grafting rate, thereby effectively improving the interfacial compatibility problem between PVDF and polar polymers.

[0035] Additional aspects and advantages of the embodiments of this application will be described and shown in part in the following description, or illustrated by practice of the embodiments of this application. Detailed Implementation

[0036] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0037] For any experimental steps or conditions not specified in the following examples and comparative examples, the procedures and conditions described in the literature in this field can be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0038] Explanation of the source of main raw materials:

[0039] PVDF is produced by Wanhua itself;

[0040] PA is produced by Wanhua itself;

[0041] SMAS-Mecklenose analytical grade;

[0042] Urea, Inokai, analytical grade;

[0043] DCP Inokai analytical grade;

[0044] AIBN Aladdin analytical grade;

[0045] AIBME Aladdin Analytical Purity;

[0046] BPO Inokai analytical grade;

[0047] DTBP Inokai analytical grade;

[0048] Sodium vinyl sulfonate, Maclean grade, analytical grade.

[0049] Example 1

[0050] The method for preparing PVDF / PA composite material in this embodiment includes the following steps:

[0051] S1. Mix PVDF (molecular weight 300,000), modified monomer SMAS, compound initiator, urea, and PA in the proportions shown in Table 1.

[0052] Table 1

[0053]

[0054]

[0055] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 170℃, first zone (low temperature grafting section) 180℃, second zone (high temperature grafting section) 210℃, discharge section 190℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw to 8 minutes by adjusting the speed by 50 rpm;

[0056] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0057] Example 2

[0058] It is basically the same as Example 1, except for the amount of each raw material used, as shown in Table 2.

[0059] Table 2

[0060] Dosage (g) 800 1200 200 10 6.65 3.35 Quality percentage 9% 0.45% 0.30% 0.15%

[0061] Example 3

[0062] It is basically the same as Example 1, except for the amount of each raw material used, as shown in Table 3.

[0063] Table 3

[0064] Dosage (g) 800 1200 200 10 7.5 2.5 Quality percentage 9% 0.45% 0.34% 0.11%

[0065] Example 4

[0066] The method for preparing PVDF / PA composite material in this embodiment includes the following steps:

[0067] S1. Mix PVDF (molecular weight 400,000), modified monomer SMAS, compound initiator, urea, and PA in the proportions shown in Table 4.

[0068] Table 4

[0069]

[0070]

[0071] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 175℃, first zone (low temperature grafting section) 185℃, second zone (high temperature grafting section) 205℃, discharge section 195℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw for 5 minutes by adjusting the speed to 100 rpm;

[0072] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0073] Example 5

[0074] The method for preparing PVDF / PA composite material in this embodiment includes the following steps:

[0075] S1. Mix PVDF (molecular weight 200,000), modified monomer SMAS, compound initiator, urea, and PA in the proportions shown in Table 5.

[0076] Table 5

[0077] Dosage (g) 800 1200 222 2.5 5 2.5 Quality percentage 10% 0.1% 0.2% 0.1%

[0078] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 165℃, first zone (low temperature grafting section) 180℃, second zone (high temperature grafting section) 215℃, discharge section 185℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel, and control the residence time of the blend in the screw to 10 minutes by adjusting the speed to 30 rpm;

[0079] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0080] Example 6

[0081] The method for preparing PVDF / PA composite material in this embodiment includes the following steps:

[0082] S1. Mix PVDF (molecular weight 300,000), modified monomer SMAS, compound initiator, urea, and PA in the proportions shown in Table 6.

[0083] Table 6

[0084]

[0085]

[0086] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 170℃, first zone (low temperature grafting section) 175℃, second zone (high temperature grafting section) 210℃, discharge section 190℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw to 8 minutes by adjusting the speed by 50 rpm.

[0087] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0088] Example 7

[0089] The method for preparing PVDF / PC composite material in this embodiment includes the following steps:

[0090] S1. Mix PVDF (molecular weight 350,000), modified monomer sodium vinyl sulfonate, compound initiator, NaCO3, and PC in the proportions shown in Table 7.

[0091] Table 7

[0092] Dosage (g) 1347 673 180 10 6.65 3.35 Quality percentage 8.1% 0.45% 0.30% 0.15%

[0093] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 165℃, first zone (low temperature grafting section) 180℃, second zone (high temperature grafting section) 215℃, discharge section 185℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel, and control the residence time of the blend in the screw to 10 minutes by adjusting the speed to 30 rpm;

[0094] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PC composite material.

[0095] Example 8

[0096] It is basically the same as Example 2, except for the amount of each raw material used, as shown in Table 8.

[0097] Table 8

[0098] Dosage (g) 800 1200 196.68 10 8.88 4.44 Quality percentage 8.9% 0.45% 0.4% 0.2%

[0099] Example 9

[0100] It is basically the same as Example 2, except for the amount of each raw material used, as shown in Table 9.

[0101] Table 9

[0102] Dosage (g) 800 1200 210 6.65 3.35 Quality percentage 9.5% 0.30% 0.15%

[0103] Example 10

[0104] It is basically the same as Example 2, except for the amount of each raw material used, as shown in Table 10.

[0105] Table 10

[0106] Dosage (g) 774 1160 266 10 6.65 3.35 Quality percentage 12% 0.45% 0.30% 0.15%

[0107] Comparative Example 1

[0108] Prepare PVDF / PA composite materials according to the following steps:

[0109] S1. Mix 800g PVDF (molecular weight 300,000) with 1200g PA;

[0110] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 170℃, first zone (low temperature zone) 180℃, second zone (high temperature zone) 210℃, discharge section 190℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw to 8 minutes by adjusting the speed by 50 rpm.

[0111] S3. The blend is obtained by water-cooled strip granulation, and the blend is dried in an oven at 80°C for 24 hours to obtain the target product PVDF / PA composite material.

[0112] Comparative Example 2

[0113] Prepare PVDF / PA composite materials according to the following steps:

[0114] S1. Mix PVDF (molecular weight 300,000), modified monomer SMAS, initiator AIBN, urea, and PA in the proportions shown in Table 11.

[0115] Table 11

[0116]

[0117]

[0118] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 170℃, grafting section 180℃, discharge section 190℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw to 8 minutes by adjusting the speed to 50 rpm.

[0119] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0120] Comparative Example 3

[0121] Prepare PVDF / PA composite materials according to the following steps:

[0122] S1. Mix PVDF (molecular weight 300,000), modified monomer SMAS, initiator DCP, urea, and PA in the proportions shown in Table 12.

[0123] Table 12

[0124] Dosage (g) 800 1200 200 10 10 Quality percentage 9% 0.45% 0.45%

[0125] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 170℃, grafting section 210℃, discharge section 190℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw to 8 minutes by adjusting the speed to 50 rpm.

[0126] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0127] Comparative Example 4

[0128] Prepare PVDF / PA composite materials according to the following steps:

[0129] S1. Mix PVDF (molecular weight 300,000), modified monomer SMAS, compound initiator, urea, and PA in the proportions shown in Table 13.

[0130] Table 13

[0131] Dosage (g) 800 1200 200 10 8 2 Quality percentage 9% 0.45% 0.36% 0.09%

[0132] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 170℃, first zone (low temperature grafting section) 180℃, second zone (high temperature grafting section) 210℃, discharge section 190℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw to 8 minutes by adjusting the speed by 50 rpm;

[0133] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0134] Comparative Example 5

[0135] Prepare PVDF / PA composite materials according to the following steps:

[0136] S1. Mix PVDF (molecular weight 300,000), modified monomer SMAS, compound initiator, urea, and PA in the proportions shown in Table 14.

[0137] Table 14

[0138] Dosage (g) 800 1200 200 10 5 5 Quality percentage 9% 0.45% 0.225% 0.225%

[0139] S2. Turn on the twin-screw extruder and set the required parameters: feeding section 170℃, low temperature grafting section 180℃, high temperature grafting section 210℃, discharge section 190℃; after the parameters of the twin-screw extruder reach the set values, place the blend into the feed barrel and control the residence time of the blend in the screw to 8 minutes by adjusting the speed to 50 rpm.

[0140] S3. The reaction product is obtained by water-cooled strip granulation. The reaction product is dried in an oven at 80°C for 24 hours to obtain the target product, PVDF / PA composite material.

[0141] Comparative Example 6

[0142] It is basically the same as Example 1, except that maleic anhydride of equal mass is used instead of SMAS.

[0143] Test case

[0144] Grafting rate test: The PVDF / polar polymer composite material was placed in DMSO solution and dissolved in an 80℃ oven for 8 hours. The liquid was then poured into an NMR tube, with the liquid level at 4-5 cm. The test sample was then... 1 H spectrum, 13 The grafting rate is calculated from the C-spectrum using the area ratio of its characteristic peaks.

[0145] Water contact angle test: The PVDF / polar polymer film was placed in a flat vulcanizing machine and pressed at 200℃ for 10 min to a sheet thickness of 0.1-0.3 mm. A 50 mm × 50 mm square sample was cut and tested using a German OCA20 surface contact angle tester. Under ambient temperature and humidity, the static contact angle of water at different locations on the film surface was measured. The droplet volume was 3 μl, and the arithmetic mean of at least 5 reading points was taken.

[0146] Peel strength test: The PVDF / PA film and PA substrate are laminated in a flat vulcanizing machine and pressed at 200℃ for 10 minutes, with a sheet thickness of 0.1-0.3 mm. The double-layer composite material is cut into standard sizes of 15 mm × 150 mm. The PVDF / PA film and PA substrate are pre-peeled 50 mm apart along the length of the sample. The sample is then fixed on a ZWICK 54 universal testing machine, and the peel speed is set to 50 mm / min. The T-peel strength is tested. If it is a PVDF / PC film, the test is performed after laminating it with a PC substrate.

[0147] Tensile strength test: PVDF / polar polymer film tensile specimens with a length of 150 mm, a width of 10.0 ± 0.2 mm, and a thickness of 4.0 ± 0.2 mm were prepared according to the testing standards. A universal electronic tensile testing machine was used for the test. The test temperature was 23℃ ± 2℃, the tensile speed was 20 ± 1 mm / min, and the specimen clamping distance was 40.00 mm, with the upper and lower clamps placed symmetrically. The specimen was clamped in the tensile testing machine clamps, ensuring that the longitudinal axis of the specimen coincided with the center line of the clamps. The testing machine was started, and the specimen was stretched at the set speed until it broke. The maximum tensile strength at which the specimen broke was recorded.

[0148] The test results are shown in Table 15, where “ / ” indicates that the item does not exist.

[0149] Table 15

[0150]

[0151]

[0152] As shown in Table 15, compared with Comparative Examples 1-5, the grafting rate of the PVDF / polar polymer composite materials prepared in all examples was significantly improved, resulting in better hydrophilicity and increased peel force between the PVDF / polar polymer film and the substrate, indicating good interfacial compatibility between PVDF and the polar polymer. Furthermore, the PVDF / polar polymer composite material prepared in this application also possesses good mechanical strength, meeting the needs of fields such as oil and gas barrier applications and pipeline transportation.

[0153] Comparing Examples 1-3, it can be seen that when the mass ratio of the first initiator to the second initiator is 2:1, the grafting rate of the composite material is the highest, the hydrophilicity is the best, and the peel force between the PVDF / PA film and the PA substrate is the greatest.

[0154] In Comparative Example 1, PVDF and PA were directly mixed and extruded. Due to the lack of grafting modification, the hydrophilicity of the PVDF / PA composite material decreased. In Comparative Example 2, only AIBN was used as the initiator; in Comparative Example 3, only DCP was used; in Comparative Example 4, DCP and AIBN were used in a 4:1 mass ratio; and in Comparative Example 5, DCP and BPO were used in a 1:1 mass ratio. All these methods resulted in decreased grafting rate, decreased hydrophilicity, and reduced peel strength. In Comparative Example 6, maleic anhydride was used instead of SMAS as the modified monomer, affecting both the hydrophilicity and peel strength of the PVDF / PA composite material.

[0155] It should be noted that the PVDF / PA film prepared in Comparative Example 1 has no adhesion to the PA substrate and separates easily when pulled during testing. Therefore, the peel force data of Comparative Example 1 in Table 15 is shown as " / ".

[0156] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this application.

Claims

1. A method for preparing a polyvinylidene fluoride / polar polymer composite material, characterized in that, Includes the following steps: S1. Mix the polar polymer, polyvinylidene fluoride, modified monomer and compound initiator to form a mixture; The compound initiator comprises a first initiator and a second initiator in a mass ratio of 1 to 3:

1. The decomposition temperature T1 corresponding to a half-life of 0.1 h for the first initiator is not lower than 110 °C, and the decomposition temperature T2 corresponding to a half-life of 0.1 h for the second initiator is less than 110 °C. The mass percentage of the compound initiator in the mixture is 0.1% to 0.5%. The modified monomer includes sodium α-alkenyl sulfonate, wherein the sodium α-alkenyl sulfonate accounts for 5% to 10% of the mass of the mixture; the polar polymer includes at least one of polyamide, polycarbonate, and polyethylene terephthalate; the mass ratio of the polar polymer to polyvinylidene fluoride is 1 to 3:

2. S2. The mixture obtained in S1 is added to the extruder and reacted sequentially in the first and second zones of the extruder. The reaction temperature in the first zone is controlled at 175℃~185℃ and the reaction temperature in the second zone is controlled at 205℃~215℃. S3. After cooling the material obtained in S2, granulate it and dry it to obtain a polyvinylidene fluoride / polar polymer composite material.

2. The method for preparing the polyvinylidene fluoride / polar polymer composite material according to claim 1, characterized in that, The first initiator includes at least one of dicumyl peroxide, di-tert-butyl peroxide, and benzoyl peroxide; And / or, the second initiator includes at least one of dimethyl azobisisobutyrate and azobisisobutyronitrile.

3. The method for preparing the polyvinylidene fluoride / polar polymer composite material according to claim 1 or 2, characterized in that, The sodium α-alkenyl sulfonate includes at least one of sodium methpropylene sulfonate, sodium propylene sulfonate, and sodium ethylene sulfonate.

4. The method for preparing the polyvinylidene fluoride / polar polymer composite material according to claim 1 or 2, characterized in that, The weight-average molecular weight of the polyvinylidene fluoride is 200,000 to 400,000.

5. The method for preparing the polyvinylidene fluoride / polar polymer composite material according to claim 1 or 2, characterized in that, The mixture of S1 also includes a stabilizer, wherein the stabilizer accounts for 0.1% to 0.45% of the mass of the mixture; And / or, the stabilizer includes at least one of urea, calcium carbonate, and sodium carbonate.

6. The method for preparing the polyvinylidene fluoride / polar polymer composite material according to claim 1, characterized in that, The reaction time in S2 is 5 to 10 minutes.

7. A polyvinylidene fluoride / polar polymer composite material prepared by the method according to any one of claims 1-6.

8. The polyvinylidene fluoride / polar polymer composite material according to claim 7, characterized in that, The polyvinylidene fluoride / polar polymer composite material is either a polyvinylidene fluoride / polyamide composite material or a polyvinylidene fluoride / polycarbonate composite material.

9. The polyvinylidene fluoride / polar polymer composite material according to claim 8, characterized in that, The grafting rate of the polyvinylidene fluoride / polar polymer composite material is not less than 5.3%.

10. The polyvinylidene fluoride / polar polymer composite material according to claim 8 or 9, characterized in that, The peel force between the polyvinylidene fluoride / polar polymer composite material and the polar polymer is not less than 4.2 N / 15 mm; And / or, the water contact angle of the polyvinylidene fluoride / polar polymer composite material is not greater than 81.4°.

Citation Information

Patent Citations

  • Domestic water-saving device

    CN2460578Y

  • Solar cell backboard and preparation method thereof, and photovoltaic module

    CN118372495A

  • Polymer electrolyte membrane having graft chains, and method for producing the same

    US20150010848A1